OTORITAS GURU PAK DAN ORANG TUA - Sensius Amon Karlau (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
The text of the Bible as the basis for implementing Christian Education (CE) has several parts that seem ambiguous in its actualization. It can be seen in three groups of CE teachers and parents with their respective understandings. The first group considers that discipline is part of realizing the authority of teachers and parents at home, which is accompanied by firm punishment. The second group believes that corporal punishment is not permitted, and the third group believes that strict discipline and corporal punishment must be implemented. Still, it needs to be accompanied by an educational aspect. If so, how should CE teachers and parents at home as educators respond to the ambiguity of Proverbs 13:24, which seems to suggest applying a strict discipline pattern? The author uses a qualitative method with a hermeneutic research library approach for text interpretation. So it can be concluded that PAK teachers and parents at home, as much as possible, apply educational patterns with a firm attitude towards children as students but still have a "loving" heart attitude in educating.